PENGARUH LUAS LAHAN TERHADAP TINGKAT KESEJAHTERAAN PETANI PADI DI KECAMATAN SRAGEN KABUPATEN SRAGEN - Kartika Ardiratna (JURNAL ILMIAH AGRITAS, 2017)
The purpose of this research was to determine the effect of lands size to the welfare of rice farmers in the district of Sragen Sragen. This research was conducted in the District of Sragen, precisely in the Village and Village Tangkil Kedungupit, Sragen, Central Java, which has been implemented from the month of April-May 2016. The samples in this research using stratified random sampling method with a sample size of 40 farmers sample of 22 farmers samples from Tangkil village and 18 farmers samples from Kedungupit village.The analytical method used is descriptive quantitative method that uses a scoring system to calculate each variable to be measured. Meanwhile, for hypothesis testing using T-Tests. The results of this research indicate that amounted to 0.00147 or 0.147% of land area influence on the level of welfare of rice farmers in the district of Sragen, which means there are no significant effects. Similarly, the acreage stratum 2 appeared to have well-being not greater than the acreage stratum 1, which means there is also no significant effect.Â Key words: Lands Size, Welfare of Rice Farmers